Disability and Normalcy as Constructs in Doris Lessing’s The Fifth Child - Subedi, Shankar (Interdisciplinary Journal of Management and Social Sciences, 2021)
This paper aims to analyze Doris Lessing’s The Fifth Child as story with a special focus on abnormal child Ben who is born with Down’s syndrome and how society fear his difference and play an important role in constructing what is termed as disability. The young English couple, Harriet and David Lavatt move from a romanticized ideal to hazardous situations with the conception and birth of the fifth child, Ben who is described throughout the novel as an animal, an alien or a kind of monstrous baby or the baby of a monster. The disabled baby exercises an evil and destructive force upon the family. The novel ends with the formerly happy couple and family scattered across England and the family members have been physically and emotionally traumatized due to the birth of the abnormal baby ‘Ben’. The mother’s desire for a unconventionally large family is also a sign of abnormality. She refuses the social and class conventions that dictate small families. She also refuses medical technologies and interventions during conception and at birth. This serves to prove that concepts like normalcy and disability are socially constructed and can be challenged. For the purpose of theory the paper draws on the ideas related to normalcy and disability from The Disability Studies Reader edited by Lennard J Davis.